A low viscosity slurry system for fabricating chromium doped yttrium aluminum garnet (Cr:YAG) transparent ceramics. Issue 14 (November 2015) - Guo, Wang; Huang, Jiquan; Lin, Yue; Huang, Qiufeng; Fei, Binjie; Chen, Jian; Wang, Wenchao; Wang, Fangyu; Ma, Chaoyang; Yuan, Xuanyi; Cao, Yongge
Abstract: We study the dependence of the rheological properties of slurries, as well as hydration reaction of the oxide powders during fabricating the transparent Cr:YAG ceramics out of Al2 O3 /Y2 O3 /Cr2 O3 powders via slip casting shaping and vacuum sintering. We demonstrated that the dispersant can absorbed the Y(III) and Al(III) species that have dissolved in the slurry, absorbed them on the surface of the undissolved oxide powders, and changes the pH and rheological property of the slurry and therefore further affect process of the slip casting and the sintering of the ceramic. By adopting appropriate dispersants, we obtained Cr:YAG ceramic with average grain size of ∼6.2 μm and in-line transmittance > 84% at 1450 nm after sintering the green samples at 1800 °C under vacuum for 40 h.